Diffusion of chemically reactive species in Casson fluid flow over an unsteady permeable stretching surface - MUKHOPADHYAY, Swati; VAJRAVELU, Kuppalapalle (Journal of hydrodynamics. Series B, 2013)
In this paper we investigate the two-dimensional flow of a non-Newtonian fluid over an unsteady stretching permeable surface. The Casson fluid model is used to characterize the non-Newtonian fluid behavior. First-order constructive/destructive chemical reaction is considered. With the help of a shooting method, numerical solutions for a class of nonlinear coupled differential equations subject to appropriate boundary conditions are obtained. For the steady flow, the exact solution is obtained. The flow features and the mass transfer characteristics for different values of the governing parameters are analyzed and discussed in detail.